THE ROLE OF DIGITALIZATION IN MICRO SMALL ENTERPRISES (STUDY ON SMALL ENTERPRISES IN MALANG CITY) - Sugangga, Rayyan; Rahman, Iradah; Hermawan, Agus; Wardana, Ludi Wishnu; Banu , Syahar; Putri, Erna D. S.; Malik, Mochammad M. (Nusantara Economics and Entrepreneurships Journals, 2023)
This article is prepared based on observations at small micro enterprises in Malang City, accompanied by literature review with the aim of knowing the condition of digitalization in micro small businesses. The results of observations in a small scope in Malang City, it appears that the use of digital marketing is not optimal from micro small businesses. Usage tends to be limited to Whatsapp, while the use of social media such as Instagram is still limited to using its features. The results of this study show that assistance and training are needed for micro small businesses in Malang City in terms of the use of digital technology, including in terms of digital marketing.